Rapid Screening of Epidemiologically Important Salmonella enterica subsp. enterica Serovars by Whole-Cell Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry - Dieckmann, Ralf (American Society for Microbiology, 2011)

(untitled)
Currently, 2,610 different Salmonella serovars have been described according to the White-Kauffmann-Le Minor scheme. They are routinely differentiated by serotyping, which is based on the antigenic variability at lipopolysaccharide moieties (O antigens), flagellar proteins (H1 and H2 antigens), and capsular polysaccharides (Vi antigens). The aim of this study was to evaluate the potential of matrix-assisted laser desorption ionization–time of flight (MALDI-TOF) mass spectrometry for rapid screening and identification of epidemiologically important Salmonella enterica subsp. enterica serovars based on specific sets of serovar-identifying biomarker ions. By analyzing 913 Salmonella enterica subsp. enterica strains representing 89 different serovars using MALDI-TOF mass spectrometry, several potentially serovar-identifying biomarker ions were selected. Based on a combination of genus-, species-, subspecies-, and serovar-identifying biomarker ions, a decision tree classification algorithm was derived for the rapid identification of the five most frequently isolated Salmonella enterica serovars, Enteritidis, Typhimurium/4,[5],12:i:-, Virchow, Infantis, and Hadar. Additionally, sets of potentially serovar-identifying biomarker ions were detected for other epidemiologically interesting serovars, such as Choleraesuis, Heidelberg, and Gallinarum. Furthermore, by using a bioinformatic approach, sequence variations corresponding to single or multiple amino acid exchanges in several biomarker proteins were tentatively assigned. The inclusivity and exclusivity of the specific sets of serovar-identifying biomarker ions for the top 5 serovars were almost 100%. This study shows that whole-cell MALDI-TOF mass spectrometry can be a rapid method for prescreening S. enterica subsp. enterica isolates to identify epidemiologically important serovars and to reduce sample numbers that have to be subsequently analyzed using conventional serotyping by slide agglutination techniques.